Development of Multimedia Interactive Learning Style Intermolecular Topics in Chemical Bonding Course - Muhammad Muchson (Pascasarjana Universitas Negeri Malang (UM), 2013)
Pengembangan Multimedia Pembelajaran Interaktif Topik Gaya Antarmolekul pada Matakuliah Ikatan Kimia Abstract: One of the topics in the course of chemical bonds in the college are intermolecular forces). Intermolecular forces will be more easily understood by the learner if visualized using dynamic microscopic representation. The representation can be packaged in the form of computer-based interactive multimedia. The purpose of this study is to develop a computer-based multimedia interactive learning topic of intermolecular forces in the course of chemical bonds. Multimedia development adopting 4D models developed by Thiagarajan, Semmel, and Semmel consists of four stages: (1) front-end analysis and task analysis, (2) multimedia design, (3) multimedia development, and (4) the distribution of multimedia. Multimedia results consisted of the development of multimedia usage instructions, introductions, presentation topics and questions. Chemistry lecturer assessment showed that the level of multimedia feasibility of the development of 95.5% in terms of content, while media expert assessment showed that the level of multimedia feasibility of the development of 88.2% in terms of appearance. Based on the assessment of experts, multimedia development outcomes feasible to use in teaching the topic of intermolecular forces. Improved student achievement before and after using multimedia development results are significant Students stated that multimedia development results effectively assist them in learning the topic of intermolecular forces. Based on the improvement of student achievement and the statement multimedia development results effectively used in learning topics intermolecular forces. Key Words: multimedia interactive learning, the topic of intermolecular forces, chemical bonds subject Abstrak: Salah satu topik dalam matakuliah ikatan kimia di perguruan tinggi adalah gaya antarmolekul (intermolecular forces). Gaya antarmolekul akan lebih mudah dipahami oleh pebelajar jika divisualisasikan menggunakan representasi mikroskopik dinamis. Representasi tersebut dapat dikemas dalam bentuk multimedia interaktif berbasis komputer. Tujuan dari penelitian ini adalah untuk mengembangkan multimedia pembelajaran interaktif berbasis komputer topik gaya antarmolekul pada matakuliah ikatan kimia. Pengembangan multimedia mengadopsi model 4D yang dikembangkan oleh Thiagarajan, Semmel, dan Semmel yang terdiri atas 4 tahap, yaitu (1) front-end analysis dan task analysis, (2) desain multimedia, (3) pengembangan multimedia, serta (4) distribusi multimedia. Multimedia hasil pengembangan terdiri atas petunjuk penggunaan multimedia, pendahuluan, pemaparan topik, dan soal. Penilaian dosen kimia menunjukkan bahwa tingkat kelayakan multimedia hasil pengembangan sebesar 95,5% dari segi isi, sedangkan penilaian ahli media menunjukkan bahwa tingkat kelayakanmultimedia hasil pengembangan sebesar 88,2% dari segi penampilan. Berdasarkan penilaian para ahli, multimedia hasil pengembangan layak digunakan dalam pembelajaran topik gaya antarmolekul. Peningkatan prestasi belajar mahasiswa sebelum dan sesudah menggunakan multimedia hasil pengembangan adalah signifikan. Mahasiswa menyatakan bahwa multimedia hasil pengembangan efektifmembantu mereka dalam pembelajaran topik gaya antarmolekul. Berdasarkan peningkatan prestasi dan pernyataan mahasiswa tersebut multimedia hasil pengembangan efektif digunakan dalam pembelajarantopik gaya antarmolekul.Kata kunci: multimedia pembelajaran interaktif, topik gaya antarmolekul, matakuliah ikatan kimia